KONSEP TOLL HOUSE MENURUT SERAPHIM ROSE DAN PERTUMBUHAN IMAN - anemala sisokhi zai (Sekolah Tinggi Teologi Baptis Medan, 2021)
The Toll House concept according to Seraphim Rose and Growth of Faith. This article discusses Toll House and the Growth of Faith which is reviewed according to the book The Soul After Death to explore one of the church's traditions inherited from the Church Fathers. This book is a book that is not known by many believers therefore this topic is rarely discussed, even in the Church. Therefore, this paper aims to invite believers to be on guard in the face of death, so that in all things can be done and done with the understanding that whatever we do now will be accounted for later. This dogmatism is supported through the book The Soul After Death and interactions with the Bible as well as other books or articles that discuss about Toll House, resulting in a growing spiritual life through Toll House tradition or doctrine. The dogmatic from Toll House reminds believers that while living in this world, we must fight to fight the evil spirits by keeping watch, purifying ourselves, living in holiness so that believers will no longer live in power. the evil one (sin) but instead directs his life toward the goal of God to create mankind that is to be similar to the image and likeness of God (Theosis).